GALILEE: AN INTERNET WEB BASED DISTANCE LEARNING SUPPORT SYSTEM - Budiman, Arthur; Lim, Resmana (Jurnal Informatika, 1999)
This paper presents a project of Web-based Distance Learning support system. The system has been built based on the Internet and World Wide Web facility. The system could be accessed with a web browser which is directed to a certain web server address so that students can do learning process just like in the real situation, such as student admissions, taking course materials, syllabus, assignments, students grades, class discussions through web, and doing online quizzes. Students could also join collaboration works by giving opinions, feedback and student produced paper/web which can be shared to the entire learning community. Therefore, it will build a collaborative learning environment where lectures together with students make constructive knowledge databases for entire learning community. This system has been developed based on Active Server Pages (ASP) technology from Microsoft which is embedded in a web server. Web pages reside in a web server which is connected to an SQL Database Server. Database server is used to store structured data such as lectures/students personal information, course lists, syllabus and its descriptions, announcement texts from lecturers, commentaries for discussion forum, student's study evaluations, scores for each assignment, quizzes for each course, assignments text from lectures, assignments which are collected by students and students contribution/materials. This system has been maintained by an administrator for maintaining and developing web pages using HTML. The administrator also does ASP scripts programming to convert web pages into active server pages. Lectures and students could contribute some course materials and share their ideas through their web browser. This web-based collaborative learning system gives the students more active role in the information gathering and learning process, making the distance students feel part of a learning community, therefore increasing motivation, comprehension and interaction with other students.